STUDI FENOMENOLOGI PENGALAMAN KOMUNIKASI KELUARGA PESERTA SEKOLAH IBU DI KELURAHAN PANARAGAN KOTA BOGOR DALAM MEMBANGUN KEHIDUPAN KELUARGA YANG HARMONIS - Syafiera Pabeleka, (2020)
Communication inside a family is significantly important. When the communication is not going well, it can cause various problems in the household. Moreover, divorce could be the worst risk. This research aims to find out how the learning process in the Sekolah Ibu could alter the participants' family communication as well as describe the changes that occurred before and after attending Sekolah Ibu. This research used a qualitative approach with a phenomenological study and Social Penetration Theory. The subject of this research is participants of Sekolah Ibu at Panaragan, Bogor. Data collection techniques were an interview and documentation study. Informant for this research obtained by the purposive sampling technique. The result shows that there were some materials which influenced the alteration on family communication of the participants, it goes until the alteration on the process of improving openness and intimacy communication in the family of Sekolah Ibu participants. The conclusion is communication with a husband as the effective communication materials as well as how to communicate with teenagers already made relations between participants and their family members more open and intimate so that they can build a harmonious family. Keywords: family communication, harmonious, experience